Energetics of a world-tour female road cyclist during a multistage race (Tour de France Femmes) - Areta, J. L.; Meehan, E.; Howe, G.; Redman, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Despite the increased popularity of female elite road cycling, research to inform the fueling requirements of these endurance athletes is lacking. In this case study, we report for the first time the energetics of a female world-tour cyclist competing in the 2023 Tour de France Femmes, an 8-day race of the Union Cycliste Internationale. The 29-year-old athlete presented with oligomenorrhea and low T3 before the race. Total daily energy expenditure assessed with the doubly labeled water technique was 7,572 kcal/day (~4.3 physical activity levels), among the highest reported in the literature to date for a female. Crank-based mean maximal power was consistent with female world-tour cyclists (5 min, mean 342 W, 4.8 W/kg; 20 min 289 W, 4.1 W/kg). The average daily energy intake measured with the remote food photography method (Stage Days 1-7) was 5,246 kcal and carbohydrate intake was 13.7 g/kg (range 9.7-15.9 g/kg), and 84 g/hr during stages, and an average fat intake of 15% of daily energy intake. An estimated 2,326 kcal/day energy deficit was evidenced in a 2.2 kg decrease in body mass. Notwithstanding the high carbohydrate intake, the athlete was unable to match the energy requirements of the competition. Despite signs of energy deficiency preexisting (oligomenorrhea and low T3), and other further developing during the race (weight loss), performance was in line with that of other world-tour cyclists and a best personal performance was recorded for the last stage. This case study emphasizes the need for further research to inform energy requirements for female athletes` optimal performance and health.